Screening for cerebrovascular disorder on the basis of family history in asymptomatic children. (3rd September 2021) - Millward, Christopher Paul; Van Tonder, Libby; Williams, Dawn; Thornton, Owen; Foster, Mitchell; Griffiths, Michael; Puthuran, Mani; Chandran, Arun; Israni, Anil; Sinha, Ajay; Kneen, Rachel; Mallucci, Conor
Abstract: Background: Cerebrovascular disorders represent a group of uncommon, heterogeneous, and complex conditions in children. We reviewed the screening practice for the detection of cerebrovascular disorder in asymptomatic children referred to our neurovascular service on the basis of a positive family history and parental and/or treating physician concern. Methods: Retrospective case-note review of referrals to our neurovascular service (July 2008–April 2018). Patients were included if the referral was made for screening, on the basis of a positive family history of cerebrovascular disorder. Symptomatic children, those with previous cranial imaging, or children under the care of a clinical geneticist (i.e. due to the child or their relative having HHT or mutations in KRIT1) were not eligible for inclusion. Results: Forty-one children were reviewed, 22 males (Median age 10.7 years, range 0.6–15.6 years). This represented 22% of the total number of referrals over a 10-year period. Twenty-nine children had an MRI/MRA brain. Twenty-eight children were referred due to a family history of intracranial aneurysm and/or subarachnoid haemorrhage, but only two had two first-degree relatives affected. Ten children were referred due to a family history of arteriovenous malformation. Three children were referred due to a family history of stroke. No cerebrovascular disease was detected during the study period ( n  = 29). Conclusions: Parental and/or physician concern generated a substantial number of referrals but no pathology was detected after screening. Whilst general screening guidance exists for the detection of intracranial aneurysms, consensus guidelines for the screening of children with a positive family history do not, but are required both to guide clinical practice and to assuage parental and/or physician concerns.